2019
DOI: 10.3906/vet-1810-60
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of milk glutathione peroxidase and superoxide dismutase levels in subclinical mastitis in Damascus goats

Abstract: The aim of this study was to evaluate milk glutathione peroxidase (GPx) and superoxide dismutase (SOD) levels in Damascus goats with subclinical mastitis. According to the somatic cell counts (SCCs), 193 Damascus goats included in the study were divided into healthy (n = 75; SCC <1000 × 10 3 cell/mL) and mastitis (n = 118; SCC ≥1000 × 10 3 cell/mL) groups. It was determined that GPx levels were 271.76 ± 3.16 U/L and 300.47 ± 9.04 U/L and SOD levels were 2.57 ± 0.09 U/mL and 2.23 ± 0.07 U/mL in the healthy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
5
4
1
Order By: Relevance
“…Our present findings are in line with previous reports (Andrei et al, 2016;Darbaz et al, 2019) that an elevated oxidative stress mediated by catalase activity might have originated either from the mammary gland and/or bacterial cells. During the pathogenesis of bovine mammary gland, bacteria are not rapidly killed by the phagocytic activity of bovine macrophages; rather, they survive within macrophages during prolonged infection due to secretion of catalase and superoxide dismutase, which by degrading H 2 O 2 , inhibit the ROS mediated killing mechanism of the host (Andrei et al, 2016;Darbaz et al, 2019). The majority of published studies on bovine mastitis describe 16S rRNA genebased community structure evaluations, whereas published reports on shotgun deep sequencing metagenomics of CM microbiome studies remain scarce.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our present findings are in line with previous reports (Andrei et al, 2016;Darbaz et al, 2019) that an elevated oxidative stress mediated by catalase activity might have originated either from the mammary gland and/or bacterial cells. During the pathogenesis of bovine mammary gland, bacteria are not rapidly killed by the phagocytic activity of bovine macrophages; rather, they survive within macrophages during prolonged infection due to secretion of catalase and superoxide dismutase, which by degrading H 2 O 2 , inhibit the ROS mediated killing mechanism of the host (Andrei et al, 2016;Darbaz et al, 2019). The majority of published studies on bovine mastitis describe 16S rRNA genebased community structure evaluations, whereas published reports on shotgun deep sequencing metagenomics of CM microbiome studies remain scarce.…”
Section: Discussionsupporting
confidence: 94%
“…Catalase activity is a marker of bovine mastitis, which plays a central role in milk redox control and markedly increases during the pathophysiology of bovine CM (Andrei et al, 2016). Our present findings are in line with previous reports (Andrei et al, 2016;Darbaz et al, 2019) that an elevated oxidative stress mediated by catalase activity might have originated either from the mammary gland and/or bacterial cells. During the pathogenesis of bovine mammary gland, bacteria are not rapidly killed by the phagocytic activity of bovine macrophages; rather, they survive within macrophages during prolonged infection due to secretion of catalase and superoxide dismutase, which by degrading H 2 O 2 , inhibit the ROS mediated killing mechanism of the host (Andrei et al, 2016;Darbaz et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has shown that milk from animals diagnosed with subclinical mastitis was characterised by an increase in GPx activity compared with healthy milk [ 87 ], and the results of the present study on goat milk are consistent with previous papers [ 88 ]. The increased enzymatic activity could be explained by both the hydrolysis of the casein-enzyme complex, which is followed by enzyme release, or by the possible pathogen’s antioxidant defense system as a survival mechanism [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, although a study conducted by Darbaz et al (2019) found that the effects of lactation order and birth type on SCC in Damascus goat milk samples were not significant, the effects of lactation order and birth type on SCC were found statistically significant in this study (p<0.01). However, according to the results of the Duncan comparison test, the effect of the third lactation order on SCC was found to be different (Table 2).…”
Section: Resultscontrasting
confidence: 91%